Cryopreservation of Granule Cells From the Postnatal Rat Hippocampus - Junya Ichikawa; Ryuji X Yamada; Rieko Muramatsu; Yuji Ikegaya; Norio Matsuki; Ryuta Koyama (Elsevier, 2007)
Although primary cultures of neurons are essential methods for cell biological and pharmacological researches, many animals must be sacrificed for each experiment. Here we introduce a novel system to cryopreserve hippocampal granule cells (GCs) prepared from postnatal rats. Being thawed after as long as 60 days of cryopreservation, GCs expressed the mature neuronal marker MAP-2 and elongated single tau-1-positive axons and multiple tau-1-negative dendrites. These properties closely resembled intact GCs in primary cultures, providing the advantage of being able to repeatedly prepare stable cultures with a single sacrifice of animals. Keywords:: dentate gyrus, primary culture, Prox1